ANALISIS INTERAKSI SOSIAL PADA PESERTA DIDIK KELAS VII SMP NEGERI 3 PONTIANAK - Yudiarti, Arini; Purwanti, Purwanti; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSocial interaction is dynamic social relations, what is meant by dynamic is that the interaction will allow an individual or group to change. When two people meet each other the social interaction begins at that time. They mutually admonish each other, shaking hands, speaking or maybe even fighting. Those activities are forms of social interaction. Although they do not speak to each other or do not exchange signs, that's where social interaction has occurred, because of each person is aware of the existence of another party which causes changes in the feelings or conditions of people are concerned.Based on the results of data analysis, research of social interaction reaches a score in the